Powdery mildew resistance in recombinat lines originating from crosses between Hordeum vulgare and Hordeum bulbosum. - Czembor, Jerzy H. (Plant Breeding and Seed Science, 2007)
Six recombinant lines obtained from crosses and backcrosses of barley cultivars (backcrossing parents) and accessions of H. bulbosum were tested with 18 differential isolates of Blumeria graminis f.sp. hordei. These lines originated from New Zealand Institute for Crop and Food Research Limited, Christchurch, New Zealand. Based on screening tests it was concluded that resistance to powdery mildew is present in all tested recombinant lines. Outstanding resistance to powdery mildew was identified in line 81882/83/3/2/9...